ANALISIS FAKTOR-FAKTOR PENGAMBILAN KEPUTUSAN PEMILIHAN KEPALA DAERAH OLEH GENERASI MILLENNIAL KABUPATEN BOGOR : Array - Fonny Meta Fernanda; Lindawati Kartika (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
On 27 June 2018 regional head elections (pilkada) were held throughout Indonesia, including the Bogor district. In Bogor district, the millennial generation reaches 58 percent of 5 587 390 people, so that the votes of the millennial generation can influence the vote for the Bogor regency Regent election. The purpose of this study was to analyze the characteristics of the millennial generation, perceptions of the participation of the millennial generation and leadership models, to analyze the factors affecting the millennial generation in the decision to elect the Regent of Bogor regency. Sources of data obtained through questionnaires, interviews, and literature review. The sampling method uses snowball and quota sampling. Data analysis used descriptive analysis, factor analysis, and net promoter score. The results showed that the factors that influence the election decision are personal factors with the indicator of the provision of new jobs for the community and the net promoter score is the detractor